UPAYA MENINGKATKAN KEMAMPUAN MENGENAL KATA SIFAT MELALUI MEDIA FOTO CLIP BAGI ANAK TUNARUNGU - Purnama Sari; Yosfan Azwandi; Kasiyati - (Jurnal Penelitian Pendidikan Khusus, 2013)
Abstrac Abstract: This research background overshadow from the problems who looks in the pitch, namely child with hearing impairment class of VI in SLB Negeri Limo Kaum Batusangkar who experiencing difficulty within get to know word the nature. Besides it researchers also held a oral test with using the ten the word the nature (sadly, embarrassed, angry, homesick, happy, hate, sick, lazy, afraid, arrogant) it turns out the result is child not yet known the word with well, namely child only get to know three word from ten word who supplied. Based on the mentioned hence this research aims for improve the ability known the word the nature for the child with hearing impairment class of VI through media Photos Clip in SLB Negeri Limo Kaum Batusangkar. Methodology research which used is Single Subject Research (SSR) with design his research is AB and technique visual analysis graphs. Subject of research is child with hearing impairment class of VI in SLB Negeri Limo Kaum Batusangkar. The results of research which analyzed will include number of observations on condition baseline (A) as many as eight times the observations visible highest value achieved is only 13.33%, the condition of intervention (B) as much as ten times the and highest value achieved 100%. From the the results of acquisition this data can be be concluded that the media Photos Clip can be be used for improve the the ability of known the word the nature. Kata-kata kunci : Mengenal Kata sifat; Media Foto Clip; Anak Tunarungu.